Stand structure adjustment influences the biomass allocation in naturally generated Pinus massoniana seedlings through environmental factors - He, Wenchun; Wang, Yu; Wang, Xiao; Wen, Xiaochen; Li, Tianyi; Ye, Mengting; Chen, Gang; Zhao, Kuangji; Hou, Guirong; Li, Xianwei; Fan, Chuan (Frontiers in Plant Science, 2022)
The natural regeneration of seedlings is a key factor for forest succession. Nevertheless, studies explaining the mechanism of growth and biomass allocation in regenerated seedlings after disturbance are lacking. Therefore, we measured the growth, biomass accumulation, and biomass allocation in current-age seedlings of Pinus massoniana after selective logging (logging of competitive trees, LCT; logging of inferior trees, LIT; and unlogged control, CK), and established structural equation models (SEMs) among the spatial structure characteristic indexes of the stand, environmental factors, and biomass allocation in different organs. As compared to the CK, the mingling index (M), uniform angle index (W), opening degree (O), soil organic carbon (SOC), available nitrogen (SAN), available phosphorus (SAP), available potassium (SAK), and bulk density (SBD) significantly increased (p < 0.05), while the competition index (CI) and neighborhood comparison (U) significantly decreased after logging (p < 0.05). After the LCT, seedling branch biomass improved, with an increase in the ground-diameter, crown-root ratio, and seedling quality index. More biomass was allocated to foliage and roots by an increase in the height and height-diameter ratio under the LIT. In the CK, increasing stem biomass helped the seedlings absorb and utilize more light. The Pearson correlation coefficient showed that biomass allocation to organs was independent, and seedlings adopted the strategies of heterogeneous adaptation and growth, thereby resulting in the separation of the allocation patterns among the organs. As per the redundancy analysis (RDA), CI was the main factor in biomass allocation. Environmental factors had direct effects on biomass allocation to organs, while the stand spatial structure characteristic indexes had indirect effects on biomass allocation based on SEMs. In summary, the LCT had significant, albeit indirect, effects on SOC, SAN, and SBD by reducing the CI for the regeneration and growth of seedlings in the stand, which was of great significance to the sustainable development of the forest stand of P. massoniana.